The Development of Islamic English Register in Pawening Madrassa - Faizal Risdianto (International Journal of English Linguistics, Literature, and Education (IJELLE), 2020)
This research is descriptive qualitative and has three research objectives: to know the forms of Islamic English Registers, Islamic English Register characteristics and the boosting force and impeding factors of the development of the Islamic English Register at Pawening Madrassa (PM), Surakarta, Indonesia. From the results of observations and interviews it can be seen the results of the study as follows: There was a direct learning strategy using Teacher-Centered-Approach and the "Army-Method" learning model. The Students’ learning model follows a Behaviorist pattern that focused on the habituation of language skills with a pattern of creating the habit of Students with a Punishment and Reward pattern. The boosting Force of the Learning Process of Islamic English Register at PM were adequate facilities, infrastructure, language learning Environment to develop Students to be able to speak and write in the Islamic English Register whereas, the impeding factor was the attitude of Students who consider trivial the given penalties of their dishonored actions.Keywords:   Register, Islamic English,Direct method, Army method, Teacher-Centered-Approach